Conceptual framework for assessing the ecotourism carrying capacity of mangrove areas at ujung piring beach, Mlonggo - Elida Farikah; Anggoro Sutrisna; Putro Sapto P.; NR Wardhani Windi (E3S Web of Conferences)
The mangrove ecosystem plays a crucial role in maintaining biodiversity and ecological functions in coastal areas. This conceptual article explores the potential of mangrove ecosystems as ecotourism destinations, focusing on the suitability assessment of the area and tourism support capacity on Kemujan Island, Karimunjawa National Park, Indonesia. The study employs land suitability evaluation and tourism capacity analysis to assess the condition of mangrove forests as natural tourist destinations. The assessment results indicate that the mangrove forests in the region have high biodiversity and facilities that support various ecotourism activities, such as trekking, nature photography, and wildlife observation. The tourism capacity evaluation also identifies that the area can accommodate a number of visitors, considering factors such as area size, types of activities, and visit duration. In conclusion, developing mangrove ecotourism could provide significant economic benefits while promoting environmental conservation, though careful management is required to ensure the sustainability of the ecosystem and the well-being of local communities.